Soda glazing - Tudball, Ruthanne (Ceramics handbooks, 2001)
"In this book, Ruthanne Tudball discusses the history of and techniques involved in soda glazing. She includes body and slip recipes, kiln designs and firing methods specifically developed for soda glazing and she illustrates her text with the work of an international group of artists"--Provided by publisher.